2002
DOI: 10.1021/jf010984r
|View full text |Cite
|
Sign up to set email alerts
|

Release of Ferulic Acid from Oat Hulls byAspergillusFerulic Acid Esterase andTrichodermaXylanase

Abstract: Oat hulls, an agricultural byproduct, contain a relatively high amount of ferulic acid (FA; 4-hydroxy-3-methoxycinnamic acid), which is believed to be inhibitory to oat hull biodegradability by rumen microorganisms. In this paper, Aspergillus ferulic acid esterase (FAE) was investigated for its ability to release FA from oat hulls. The objectives were to determine the effects of particle size of oat hulls (ground to pass through 1 mm and 250 microm screens and a 100 microm sieve) on release of FA by FAE both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 45 publications
(92 reference statements)
2
52
1
2
Order By: Relevance
“…The present and previous investigations (Yu et al 2000(Yu et al , 2002 have shown that a ferulic acid esterase, A-FAE, had no detectable activity toward oat hulls that were ground to pass through a 1-mm screen, but had low levels of activity toward very finely ground (250 and 100 µm) oat hulls, suggesting that substrate size and/or accessibility impedes enzyme activity.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The present and previous investigations (Yu et al 2000(Yu et al , 2002 have shown that a ferulic acid esterase, A-FAE, had no detectable activity toward oat hulls that were ground to pass through a 1-mm screen, but had low levels of activity toward very finely ground (250 and 100 µm) oat hulls, suggesting that substrate size and/or accessibility impedes enzyme activity.…”
Section: Discussioncontrasting
confidence: 45%
“…Oat hulls contain relatively high amounts of hydroxycinnamic acids, mainly ferulic acid (3-methoxy-4-hydroxycinnamic acid) and p-coumaric acid (4-hydroxycinnamic acid) (Garleb et al 1987(Garleb et al , 1991 at levels of 0.4 to 0.5% and 0.3 to 0.4%, respectively (Garleb et al 1991;Yu et al 2000Yu et al , 2002. They are covalently cross-linked to polysaccharides by ester bonds and to components of lignin, mainly by ether bonds (Scalbert et al 1985;Borneman et al 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with this enzyme preparation can effectively release the cinnamic acid derivatives. Some studies have demonstrated that a combination of ferulic acid esterase and endoxylanase released ferulic acid from de-starched wheat bran (Faulds and Williamson, 1991) and oat hulls (Yu et al, 2002(Yu et al, , 2003. Therefore, the fi ndings of the present study indicate enzyme preparations from S. commune may provide a novel method for utilization of unused agricultural wastes.…”
Section: Discussionmentioning
confidence: 57%
“…In monocots, ferulic acid is esterified to the C-5 hydroxyl group of arabinofuranose residues of arabiboxylans (Colquhoun et al 1994;Ralet et al 1994;Saulnier et al 1995b;Ishii 1997;Wende and Fry 1997a, b, c) such as in wheat bran, oat hulls (Yu et al 2002a), barley straw, and maize (Faulds and Williamson 1995;Faulds et al 1995a;Saulnier et al 1995a).…”
Section: Ferulic Acid In Monocotsmentioning
confidence: 99%